The impact of servant leadership perceptions on employees’ job burnout levels - Marques, Carina Isabel da Silva (2022)
In the current work context, constantly changing and increasingly demanding, in which employees’ well-being is often at risk, leaders have become increasingly important. In this context, a positive leadership style, such as servant leadership, which postulates that the leader is a source of resources and support, and that the main priority are employees’ needs, might contribute to decreasing the negative effects of job burnout, both on the individual and organisational levels. Therefore, this research aims at studying the impact that servant leadership perceptions have on employees’ job burnout levels. The sample is composed of 79 participants from different organisations and sectors. The results show that servant leadership perceptions have a negative impact on employees’ job burnout levels, being that impact stronger when the leader is male. The results not only confirm the importance of leadership within the organisational environment and to employees’ well-being, but also add to the literature about the impact of servant leadership on employees’ well-being and the influence of the gender of the leader in such relationship.